Individual Responsibility as a Protection Measure in Mexico Against the Covid-19 - Bañuelos, Jesús Francisco Ramírez (Journal of Leadership, Accountability and Ethics, 2021)
Using a legal philosophy approach, this article seeks to reflect on individual responsibility as a protection measure implemented in Mexico to address the Covid-19 pandemic. The #StayHome strategy is studied as an imperfect legal norm that structures the government's reaction in the country to protect the human right to health of the inhabitants of Mexican territory in the context of the health crisis. Subsequently, the opportunity is considered for the (in)action of individuals under a scheme of individual responsibility in order to avoid the spread of contagion and to have a beneficial impact on the natural process of the epidemic. The conclusion is that despite having an explicit regulatory framework of an executive nature, the Government of Mexico has decided to address the health crisis in terms of reducing infections with a strategy based on two aspects: the first, the socialized measure of #StayAtHome and the second, the transfer of health protection measures to individuals.